2018
DOI: 10.3389/fimmu.2018.01306
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Stress Responses to Bacterial Pathogenesis Patterns

Abstract: Activation of an appropriate innate immune response to bacterial infection is critical to limit microbial spread and generate cytokines and chemokines to instruct appropriate adaptive immune responses. Recognition of bacteria or bacterial products by pattern recognition molecules is crucial to initiate this response. However, it is increasingly clear that the context in which this recognition occurs can dictate the quality of the response and determine the outcome of an infection. The cross talk established be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 111 publications
0
17
0
Order By: Relevance
“…Indeed, multiple endogenous and exogenous stressors influence protein synthesis by initiating signaling cascades that lead to the attenuation of translation ( Fig. 1; García et al, 2007;Grant, 2011;Harding et al, 1999Harding et al, , 2003Liu et al, 2008;Rodrigues et al, 2018). Activation of the integrated stress response (ISR; Bernales et al, 2006;Harding et al, 2000) or inhibition of mechanistic/mammalian target of rapamycin (mTOR; Ben-Sahra and Manning, 2017;Hay and Sonenberg, 2004;Shimobayashi and Hall, 2014;Yoon, 2017) are well-established stress response pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple endogenous and exogenous stressors influence protein synthesis by initiating signaling cascades that lead to the attenuation of translation ( Fig. 1; García et al, 2007;Grant, 2011;Harding et al, 1999Harding et al, , 2003Liu et al, 2008;Rodrigues et al, 2018). Activation of the integrated stress response (ISR; Bernales et al, 2006;Harding et al, 2000) or inhibition of mechanistic/mammalian target of rapamycin (mTOR; Ben-Sahra and Manning, 2017;Hay and Sonenberg, 2004;Shimobayashi and Hall, 2014;Yoon, 2017) are well-established stress response pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Other changes in the cell sensed by innate receptors are membrane damage; for example, some enteroinvasive bacteria can induce depletion of amino acids by membrane damage, resulting in the activation of mammalian target of rapamycin (mTOR)-controlled autophagy or the integrated stress response via the general control non-de-repressible 2 kinase (GCN2, EIF2AK4), as demonstrated in Shigella-infected human cell lines [52]. Many bacteria, including Brucella abortus and Chlamydia muridarum, are known to induce endoplasmic reticulum (ER) stress responses, resulting in activation of the unfolded protein response (UPR) effectors, inositol-requiring enzyme (IRE)1α, ATF6, and PRKR-like endoplasmic reticulum kinase (PERK) (Figure 1) [53]. Upon mouse infection with Brucella and Chlamydia, UPR can ultimately lead to the activation of inflammatory pathways by an IREα-mediated TRAF2-NOD1/2 pathway that is independent of NOD1/2-mediated peptidoglycan sensing [54].…”
Section: Sensing Of Cellular Stressmentioning
confidence: 97%
“…Indeed, Salmonella, Shigella, and Listeria infection were shown to induce eIF2a phosphorylation [24][25][26] thereby demonstrating that ISR activation occurs as a result of patterns of bacterial pathogenesis such as bacterial growth, membrane damage, access to cytosol, and cytoskeleton disruption (see for review Ref. [27]). Moreover, Shresta et al have reported that cells lacking HRI are highly resistant to infection by bacterial pathogens, including Yersinia, Chlamydia, and Listeria [28].…”
Section: Requirement Of the Hri-eif2a Axis For The Isrmediated Inflammentioning
confidence: 99%